Jimmy Neutron, boy genius [videorecording (DVD)]. - Davis, John A.; Stewart, Patrick, 1940-; Short, Martin, 1950- (Paramount Home Entertainment, 2002)
A 10-year-old boy and his robot dog battle evil, rescue his parents, save the Earth...and get home in time for dinner.